Reference Manual on Scientific Evidence: Third Edition - National Research Council (The National Academies Press, 2011)
The Reference Manual on Scientific Evidence, Third Edition, assists judges in managing cases involving complex scientific and technical evidence by describing the basic tenets of key scientific fields from which legal evidence is typically derived and by providing examples of cases in which that evidence has been used. First published in 1994 by the Federal Judicial Center, the Reference Manual on Scientific Evidence has been relied upon in the legal and academic communities and is often cited by various courts and others. Judges faced with disputes over the admissibility of scientific and technical evidence refer to the manual to help them better understand and evaluate the relevance, reliability and usefulness of the evidence being proffered. The manual is not intended to tell judges what is good science and what is not. Instead, it serves to help judges identify issues on which experts are likely to differ and to guide the inquiry of the court in seeking an informed resolution of the conflict. The core of the manual consists of a series of chapters (reference guides) on various scientific topics, each authored by an expert in that field. The topics have been chosen by an oversight committee because of their complexity and frequency in litigation. Each chapter is intended to provide a general overview of the topic in lay terms, identifying issues that will be useful to judges and others in the legal profession. They are written for a non-technical audience and are not intended as exhaustive presentations of the topic. Rather, the chapters seek to provide judges with the basic information in an area of science, to allow them to have an informed conversation with the experts and attorneys.

New Directions in Child Abuse and Neglect Research - Institute of Medicine; National Research Council (The National Academies Press, 2014)
Each year, child protective services receive reports of child abuse and neglect involving six million children, and many more go unreported. The long-term human and fiscal consequences of child abuse and neglect are not relegated to the victims themselves2014they also impact their families, future relationships, and society. In 1993, the National Research Council (NRC) issued the report, Under-standing Child Abuse and Neglect, which provided an overview of the research on child abuse and neglect. New Directions in Child Abuse and Neglect Research updates the 1993 report and provides new recommendations to respond to this public health challenge. According to this report, while there has been great progress in child abuse and neglect research, a coordinated, national research infrastructure with high-level federal support needs to be established and implemented immediately. New Directions in Child Abuse and Neglect Research recommends an actionable framework to guide and support future child abuse and neglect research. This report calls for a comprehensive, multidisciplinary approach to child abuse and neglect research that examines factors related to both children and adults across physical, mental, and behavioral health domains2014including those in child welfare, economic support, criminal justice, education, and health care systems2014and assesses the needs of a variety of subpopulations. It should also clarify the causal pathways related to child abuse and neglect and, more importantly, assess efforts to interrupt these pathways. New Directions in Child Abuse and Neglect Research identifies four areas to look to in developing a coordinated research enterprise: a national strategic plan, a national surveillance system, a new generation of researchers, and changes in the federal and state programmatic and policy response.

The Polygraph and Lie Detection - National Research Council (The National Academies Press, 2003)
The polygraph, often portrayed as a magic mind-reading machine, is still controversial among experts, who continue heated debates about its validity as a lie-detecting device. As the nation takes a fresh look at ways to enhance its security, can the polygraph be considered a useful tool? The Polygraph and Lie Detection puts the polygraph itself to the test, reviewing and analyzing data about its use in criminal investigation, employment screening, and counter-intelligence. The book looks at: The theory of how the polygraph works and evidence about how deceptiveness2014and other psychological conditions2014affect the physiological responses that the polygraph measures. Empirical evidence on the performance of the polygraph and the success of subjects' countermeasures. The actual use of the polygraph in the arena of national security, including its role in deterring threats to security. The book addresses the difficulties of measuring polygraph accuracy, the usefulness of the technique for aiding interrogation and for deterrence, and includes potential alternatives2014such as voice-stress analysis and brain measurement techniques.

Reforming Juvenile Justice: A Developmental Approach - National Research Council (The National Academies Press, 2013)
Adolescence is a distinct, yet transient, period of development between childhood and adulthood characterized by increased experimentation and risk-taking, a tendency to discount long-term consequences, and heightened sensitivity to peers and other social influences. A key function of adolescence is developing an integrated sense of self, including individualization, separation from parents, and personal identity. Experimentation and novelty-seeking behavior, such as alcohol and drug use, unsafe sex, and reckless driving, are thought to serve a number of adaptive functions despite their risks. Research indicates that for most youth, the period of risky experimentation does not extend beyond adolescence, ceasing as identity becomes settled with maturity. Much adolescent involvement in criminal activity is part of the normal developmental process of identity formation and most adolescents will mature out of these tendencies. Evidence of significant changes in brain structure and function during adolescence strongly suggests that these cognitive tendencies characteristic of adolescents are associated with biological immaturity of the brain and with an imbalance among developing brain systems. This imbalance model implies dual systems: one involved in cognitive and behavioral control and one involved in socio-emotional processes. Accordingly adolescents lack mature capacity for self-regulations because the brain system that influences pleasure-seeking and emotional reactivity develops more rapidly than the brain system that supports self-control. This knowledge of adolescent development has underscored important differences between adults and adolescents with direct bearing on the design and operation of the justice system, raising doubts about the core assumptions driving the criminalization of juvenile justice policy in the late decades of the 20th century. It was in this context that the Office of Juvenile Justice and Delinquency Prevention (OJJDP) asked the National Research Council to convene a committee to conduct a study of juvenile justice reform. The goal of Reforming Juvenile Justice: A Developmental Approach was to review recent advances in behavioral and neuroscience research and draw out the implications of this knowledge for juvenile justice reform, to assess the new generation of reform activities occurring in the United States, and to assess the performance of OJJDP in carrying out its statutory mission as well as its potential role in supporting scientifically based reform efforts.